Metal and Metal Oxide Based Advanced Ceramics for Electrochemical Biosensors-A Short Review - Subbaiah, G. Bala; Ratnam, K. Venkata; Janardhan, S.; Shiprath, K.; Manjunatha, H.; Ramesha, M.; Prasad, N. V. Krishna; Ramesh, S.; Babu, T. Anil (Frontiers in Materials, 2021)
Identifying and quantification of biological concentrations of certain biomolecules such as dopamine, glucose, tyrosine, cholesterol etc. has become the basis of medical diagnosis in the treatment of related diseases. In most of the cases, the concentrations of these biomolecules in biofluids like blood acts as biomarkers and becomes crucial in the treatment of diseases. On the other hand, advanced ceramics refers to oxides (alumina, zirconia), non-oxides: (carbides, borides, nitrides, silicides), Composites (particulate reinforced combinations of oxides and non-oxides), etc. This review article discusses about recent developments in the field of electrochemical sensors developed using metal and metal oxide based advanced ceramics with an emphasis on developments in the field for the past five years. The article presents the key results, important findings, interesting chemistry of biosensing of advanced ceramic based electrochemical biosensors for some important biomolecules such as acetaminophen, glucose, dopamine etc.